2023
DOI: 10.31577/km.2023.2.121
|View full text |Cite
|
Sign up to set email alerts
|

Austempering Ce-La inoculated solution strengthened ferritic ductile cast irons

Abstract: The influence of austempering conditions on the microstructure, hardness, tensile strength, and impact toughness of Ce-La inoculated solution-strengthened ferritic ductile irons was analyzed. The austempering was performed at temperatures 280, 320, 420, 520, and 620 • C for periods of 1.5 and 2.5 h. Metallurgical characterization of the samples was determined using scanning electron microscopy, optical microscopy, X-ray diffraction, microhardness, impact, and tensile test. The fracture surfaces of the tensile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…It was reported that through appropriate heat treatment processes, the impact toughness of ductile iron under low-temperature conditions can be markedly enhanced, thereby avoiding the brittle fracture. This innovative approach can make much wider applications for ductile iron [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that through appropriate heat treatment processes, the impact toughness of ductile iron under low-temperature conditions can be markedly enhanced, thereby avoiding the brittle fracture. This innovative approach can make much wider applications for ductile iron [16][17][18].…”
Section: Introductionmentioning
confidence: 99%